Correcting Consumer Misperceptions about CO₂ Emissions - Taisuke Imai; Davide D. Pace; Peter Schwardmann; Joël van der Weele (Center for Economic Studies and ifo Institute (CESifo), 2022)
Policy makers put great emphasis on the role of information about carbon emissions in achieving sustainable decisions by consumers. We conduct two studies to understand the optimal targeting of such information and its effects. First, we conduct an incentivized and representative survey among US consumers (N = 1, 022) to investigate awareness of climate impact and willingness to mitigate it. We find a large variation in the perceptions of the carbon emissions of different consumption behaviors, with an overall tendency to underestimate these emissions. We also find a positive but highly concave willingness to mitigate climate impact. We combine elicited misperceptions and willingness to mitigate in a structural model that delivers sharp predictions about where to best target information campaigns. In an experiment with actual consumption decisions (N = 2, 081), we then test for the effect of CO2 information on the demand for beef, a product predicted to be a productive target for information. Correcting misperceptions has no effect on the demand for beef, both in absolute terms and compared to a predictably less productive target of information, i.e. the demand for poultry. Our dataset allows us to hone in on the underlying reason for this null effect.
Keywords: C81; C93; D84; Q54; 330; climate change; carbon emissions; information provision; consumer behavior